IMPLEMENTASI CONTENT MANAGEMENT SYSTEM UNTUK PEMBUATAN WEBSITE OFFICIAL PERGURUAN TINGGI: CMS;Web Official;College. - Purnama, Fery; Rini, Faiza; Tamrin Syah (LP2M Universitas Nurdin Hamzah, 2022)
College official website is an official website owned by a university that is used to convey information online. Currently the development of technology is very rapid and fast, starting from the development of programming languages, security and server changes that continue to increase all the time making it very difficult for some webmasters to keep up with very fast changes. The Content Management System provides many conveniences and advantages in building an official website. In the content management system, there are already various features that are very good at developing official webs in terms of updating features and technology easily, good SEO and also very good security. One of the popular content management systems today is Joomla because currently Joomla supports nearly 2 million websites on the internet. Joomla is a type of CMS (Content Management System) which is open source and based on PHP and MySQL. This platform offers various advanced features that will help the process of creating a website or application easily. To overcome the rapid development of programming language and security technology, the researchers built an official university website using the Joomla CMS to make it easier to update and upgrade the features available on the website later. With the official web using Joomla CMS, it is hoped that the website will be more powerful, stable, well indexed SEO and ease of updating and upgrading when changes and improvements occur from the server and technology side.